Analisis Risiko dan Determinan Kejadian Kecelakaan Kerja di Pabrik Minyak Kelapa Sawit - Eka Rini, Willia Novita; Aswin, Budi; Hidayati, Fajrina (Jurnal Riset Hesti Medan, 2021)
Safety at work is a series of safety related to machines, work tools, materials and work processes, workplace and environment as well as working methods. Jambi Province is an area that has extensive plantation land, especially for oil palm plantations, based on data from the Central Bureau of Statistics at Provinceof Jambi in 2018. PT. X was experienced the highest incidence of work accidents in the 2017-2019 range in Jambi Province. This study aims to analyze the risks and determinants of workplace accidents at the palm oil mill at PT. X as an effort to prevent work accidents. This research is analytical research. The population of this study were all workers in the production division of PT. X as many as 96 people consisting of two work shifts and were also used as samples in this study. The data will be analyzed to see the relationship between variables using the Chi-Square test with (Î± = 0.05). There is a relationship between the availability of personal protective equipment (PPE), environmental factors and the use of personal protective equipment (PPE) with the incidence of work accidents in the production division workers of PT. X while working period, attitude, training and equipment safety are not related in this study.